The relation between dizziness and suspected obstructive sleep apnoea - Maas, Britta D. P. J.; Bruintjes, Tjasse D.; van der Zaag-Loonen, Hester J.; van Leeuwen, Roeland B. (European archives of oto-rhino-laryngology, 2020)
Purpose (1) To determine the prevalence of a high risk of obstructive sleep apnoea (OSA) in patients with dizziness. (2) To assess a relation between the risk of OSA and dizziness-related impairment. (3) To determine whether a high risk of OSA is associated with unexplained dizziness or with hyperventilation/anxiety disorders. Methods In this cross-sectional study, we included Dutch adult patients with dizziness. Patients suffering from dementia were excluded. We asked patients to complete the Dizziness Handicap Inventory (DHI) and STOP-Bang questionnaire (SBQ). Based on the SBQ, patients were subdivided into groups with a low, intermediate, and high risks of OSA. All patients were subjected to our standard examinations for the workup for dizziness. Results Among 704 included patients with a mean age of 59 years (± 17 years), 258 (37%) were male. A high risk of OSA was present in 144 (20%) of our patients of whom 120 (83%) were male. Male patients with a high risk of OSA reported an on average 9-point higher score on the DHI than male patients with a low risk of OSA ( p = 0.018). We determined an independent relation between the risk of OSA and dizziness-related impairment. We observed no relation between a high risk of OSA and unexplained dizziness or hyperventilation/anxiety disorders. Conclusion The prevalence of a high risk of OSA in male patients with dizziness is high and a higher risk of OSA is associated with more dizziness-related impairments. A high risk of OSA is not associated with unexplained dizziness or with hyperventilation/anxiety disorders.